2018
DOI: 10.1002/pros.23534
|View full text |Cite
|
Sign up to set email alerts
|

Earlier use of androgen receptor‐axis‐targeted drugs may improve overall survival in patients with non‐metastatic castration‐resistant prostate cancer

Abstract: Early use of ARAT may improve OS, PFS, and PSA response in CRPC. Larger, prospective studies will be required to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The prognosis of CRPC patients with lymph node metastases is poor, the median OS of which is estimated only 31.6 months (8). Apalutamide and enzalutamide are preferred to treat nmCRPC for the encouraging results from the PROSPER trial and the SPARTAN trial, and earlier use of androgen receptor-axis-targeted drugs (ARAT) may improve OS, PFS, and PSA response (9). However, the PROSPER trial does not clarify the nodal status of the patients enrolled, while the SPARTAN trial excludes patients with lymph nodes more than 2 cm.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of CRPC patients with lymph node metastases is poor, the median OS of which is estimated only 31.6 months (8). Apalutamide and enzalutamide are preferred to treat nmCRPC for the encouraging results from the PROSPER trial and the SPARTAN trial, and earlier use of androgen receptor-axis-targeted drugs (ARAT) may improve OS, PFS, and PSA response (9). However, the PROSPER trial does not clarify the nodal status of the patients enrolled, while the SPARTAN trial excludes patients with lymph nodes more than 2 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Currently there is one retrospective analysis showing an OS benefit of early use of ARAT in nmCRPC vs mCRPC. The study demonstrated better OS from the time of diagnosis of CRPC in Kaplan-Meier analysis (median OS of 86 months vs 40 months; p = 0.004), with significant improvement observed for PFS ( p =0.048) and PSA response ( p =0.0014) [42]. Multivariate analysis demonstrated nonmetastatic status, low PSA, and long PSA doubling time at ARAT initiation as significant predictors of longer OS ( p =0.044, 0.0001, and 0.026, respectively) [42].…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated better OS from the time of diagnosis of CRPC in Kaplan-Meier analysis (median OS of 86 months vs 40 months; p = 0.004), with significant improvement observed for PFS ( p =0.048) and PSA response ( p =0.0014) [42]. Multivariate analysis demonstrated nonmetastatic status, low PSA, and long PSA doubling time at ARAT initiation as significant predictors of longer OS ( p =0.044, 0.0001, and 0.026, respectively) [42]. However, the study had a low number of patients, imbalance in imaging schedules between the two groups, and patients in the mCRPC group had higher-risk features.…”
Section: Discussionmentioning
confidence: 99%
“…New androgen receptor-axis-targeted agents (ARAT) have improved the prognosis of men with CRPC patients. Although ARAT improves survival in CRPC patients, 2 they remain incurable and eventually progress. A new approach to hormonal therapy is necessary.…”
Section: Introductionmentioning
confidence: 99%